2020
DOI: 10.1371/journal.pone.0236552
|View full text |Cite
|
Sign up to set email alerts
|

Consistent condom use among men who pay for sex in sub-Saharan Africa: Empirical evidence from Demographic and Health Surveys

Abstract: Background Paying for sex has often been associated with risky sexual behavior among heterosexual men, and men who pay for sex are considered as a bridging population for sexually transmitted infections. Consistent condom use during paid sex is essential for reducing sexually transmitted infections, including HIV/AIDS. In this study, we assessed the prevalence and predictors of consistent condom use among men who pay for sex in sub-Saharan Africa. Materials and methods We pooled data from 29 sub-Saharan Africa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 55 publications
0
5
1
Order By: Relevance
“…Improving access to treatment for men who pay for sex is especially important as, from 2010 onwards, only 68% of men used a condom the last time they paid for sex. A recent analysis of 29 DHS surveys from 2010-2019 found that, among men who reported condom use at their last paid sex, 84% reported consistent condom use during paid sex [43], which is higher than our estimates. Since the survey instruments only asked about consistent condom use if men reported condom use at last paid sex, we would expect consistent condom use measures to be higher.…”
Section: Plos Medicinecontrasting
confidence: 96%
“…Improving access to treatment for men who pay for sex is especially important as, from 2010 onwards, only 68% of men used a condom the last time they paid for sex. A recent analysis of 29 DHS surveys from 2010-2019 found that, among men who reported condom use at their last paid sex, 84% reported consistent condom use during paid sex [43], which is higher than our estimates. Since the survey instruments only asked about consistent condom use if men reported condom use at last paid sex, we would expect consistent condom use measures to be higher.…”
Section: Plos Medicinecontrasting
confidence: 96%
“…For sex workers that obtain an income and have control over that income, they can be considered financially autonomous. Yet their power to negotiate safer sex practices may vary and may be dependent upon client demographics such as age and wealth quintile (Ahinkorah et al, 2020). Further, it is not uncommon for sex workers to be subject to physical violence in Zambia (Malama et al, 2019), dismissing any ability to negotiate the terms of engagement.…”
Section: Discussionmentioning
confidence: 99%
“…(19) Additionally, a pooled analysis of Demographic and Health Survey data from 29 sub-Saharan African countries found that consistent condom use among men paying for sex was overall high, 84.0% (CI: 80.4-87.6), but varied by demographic characteristics. (20) High levels of condom use with sex workers may help to partially explain this unanticipated nding; however, additional research is needed to further explore this association in this setting.…”
Section: Discussionmentioning
confidence: 99%